Evidence of the intensification of work in the health area (Research, Society and Development, 2022)
The objective of the present study is to identify the scientific evidence about the intensification of work from the perspective of health team professionals. This is an Integrative Literature Review study, whose bibliographic survey was carried out in August and September 2020, in the following databases: Web of Science, Sci Verse Scopus (SCOPUS), Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF) and Medical Literature Analysis and Retrieval System Online (MEDLINE), via the Virtual Health Library (VHL) portal. Data were systematized using the Thematic Content Analysis technique. The sample consisted of 10 articles, with a predominance of publications in the years 2013, 2016, 2017, 2019, with the participants being health workers. The studies explained about work, linking them with health professionals, and also showed that the intensification of work is present in the daily lives of these professionals, thus causing a variety of problems that not only lead to physical health, but also psychological ones. workers.